The Islamic law of war justifications and regulations - Al-Dawoody, Ahmed 1973- (Palgrave series in Islamic theology, law, and history, 2011)
Al-Dawoody examines the justifications and regulations for going to war in both international and domestic armed conflicts under Islamic law. He studies the various kinds of use of force by both state and non-state actors in order to determine the nature of the Islamic law of war